2009
DOI: 10.3382/ps.2008-00221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of providing light during incubation on the health, productivity, and behavior of broiler chickens

Abstract: Environmental stimuli present during incubation can affect the behavior and health of birds posthatch. Commercial broiler chickens are often incubated in complete darkness, receiving light only intermittently when the incubator is opened. To determine the effect of providing light during the prehatch period, we incubated Cobb broiler eggs (n = 664) under continuous light (24L:0D), no light (0L:24D), or 12 h of light (12L:12D); the light level was 550 lx. Various parameters were measured posthatch in these broi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 47 publications
4
52
0
Order By: Relevance
“…This further indicate that specific wavelengths may be important in avian development and furthermore that illumination schedules and other factors may also play a role. It has been documented that timing and onset of light exposure during incubation is important for post-hatch effects (Archer et al, 2009;Chiandetti et al, 2013;Mench, 2014a and2014b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This further indicate that specific wavelengths may be important in avian development and furthermore that illumination schedules and other factors may also play a role. It has been documented that timing and onset of light exposure during incubation is important for post-hatch effects (Archer et al, 2009;Chiandetti et al, 2013;Mench, 2014a and2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Providing light during incubation has previously been observed to improve bird welfare post-hatch by reducing fear responses and decreasing stress susceptibility (Archer et al, 2009;Özkan et al, 2012;Archer and Mench, 2013, 2014aand 2014bHuth and Archer, 2015). This present study confirmed the previous research findings that white light exposure during incubation can improve welfare by reducing fear responses and decreasing stress susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations